Clinical Profile of Brain Tumour in Children - Sharmin, Shakila; Begum, Nazma; Khatoon, Soofia (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: This study was designed to evaluate the clinical profile and location of brain tumours in children so that brain tumour cases could be diagnosed and managed earlier. Materials and Methods: This cross sectional study was carried out from April 2011 to April 2012. A total 50 clinically suspected cases of brain tumour and supported by MRI were enrolled in this study. Results: Brain tumour of children was predominant in male where male to female ratio was almost 1.9:1. Supratentorial and Infratentorial brain tumour were found in 36% and 64% cases respectively in children. According to MRI findings in the supratentorial location, craniopharyngioma were commonest (50%) followed by cerebral astrocytoma (22.2%). In the infratentorial region, medulloblastoma was observed in (40.6%), followed by cerebellar astrocytoma (31.3%). Vertigo, weakness of limbs were found in 46.9% and 87.5% cases respectively in infratentorial group which were significantly (p<0.05) higher than supratentorial group. Growth failure and behavioral change were found in 16.7% and 22.2% cases respectively in supratentorial which were significantly (p<0.05) higher than infratentorial group. Papilloedema, reduced muscle power, increased muscle tone, exaggerated deep reflexes, clonus, gait disturbance and cerebellar signs were significantly (p<0.05) higher in infratentorial group. Conclusion: Craniopharyngioma and medulloblastoma were more common findings in MRI evaluation in the supratentorial and infratentorial location respectively. Growth failure and behavioral change were found higher in supratentorial than infratentorial group. Vertigo, weakness of limbs, papilloedema, reduced muscle power, increased muscle tone, exaggerated deep reflexes, clonus, gait disturbance and cerebellar signs were higher in infratentorial group. J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 8-12